Analisis Tekno-Ekonomi dari Refuse Derived Fuel (RDF) sebagai Waste To Energy (WTE) di TPA Pakusari Jember, Jawa Timur - Christanti, Eka Yulia Indri; Kumara, I Nyoman Satya; Partha, Cokorde Gede Indra (Majalah Ilmiah Teknologi Elektro, 2022)
The problem with waste in Jember Regency is that waste management has not been maximized. The abundant availability of combustible waste can be used as RDF as waste to energy. This study analyzed the potential RDF and the feasibility of constructing a PLTSa at TPA Pakusari using the life cycle cost method and the electricity cost is calculated by LCoE. Waste management of refuse-derived fuel in order to meet the quality standards of RDF is carried out by pre-treatment in the form of sorting, enumeration, natural or mechanical drying, and sifting. The capacity of RDF is 83.762 kg/day, with a potential power generated using gasification technology of 1.000.621 Watt. The level of GHG emissions produced is 1,8 tCO2. The PLTSa project plan is equipped with an air pollution management unit. The results of the economic analysis show that the LCC value during a lifetime is Rp. 75.903.806.400. The feasibility of the Pakusari PLTSa development plan is declared feasible with a PBP value of 13 years. The NPV value with an interest rate of 8,5% is Rp. 22.065.398.707, and the IRR value is 14,35%. In the profitability index and net B/C criteria, the project is declared feasible with a value of 2,3.